2017
DOI: 10.1200/jco.2016.72.0177
|View full text |Cite
|
Sign up to set email alerts
|

Revisions to the International Neuroblastoma Response Criteria: A Consensus Statement From the National Cancer Institute Clinical Trials Planning Meeting

Abstract: Purpose More than two decades ago, an international working group established the International Neuroblastoma Response Criteria (INRC) to assess treatment response in children with neuroblastoma. However, this system requires modification to incorporate modern imaging techniques and new methods for quantifying bone marrow disease that were not previously widely available. The National Cancer Institute sponsored a clinical trials planning meeting in 2012 to update and refine response criteria for patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
260
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 255 publications
(264 citation statements)
references
References 66 publications
0
260
0
4
Order By: Relevance
“…Kushner et al demonstrated the superiority of 123 I-MIBG for detecting relapse in routine (every 2–4 months) monitoring of high-risk patients 28 . In early-phase trials, the times to relapse/progression may artificially cluster around the times that disease assessments are typically performed or dictated by the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Kushner et al demonstrated the superiority of 123 I-MIBG for detecting relapse in routine (every 2–4 months) monitoring of high-risk patients 28 . In early-phase trials, the times to relapse/progression may artificially cluster around the times that disease assessments are typically performed or dictated by the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…They received between 2 and 11 (median 4) cycles of chemotherapy before surgery. However, only 4 (26.7%) patients showed tumor size reduction, with Response Evaluation Criteria in Solid Tumors >30% of the longest dimension after chemotherapy 5. The rest remained as massive tumors that posed challenges to surgical resection.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the scores assigned after induction therapy are prognostic of outcome of high‐risk patients treated with prior treatment regimens. Curie scores are included in the recently published INRC response criteria and provide important information for treatment decisions . Tracking specific MIBG‐positive lesions over time is likely to enhance accurate response assessment, provide additional prognostic information, and may ultimately lead to more informed treatment decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in an International Society of Pediatric Oncology European Network (SIOPEN) high‐risk study, researchers were able to validate that patients with a Curie score of ≤2 postinduction have significantly better EFS . Although the prognostic value of Curie scores has not yet been validated in high‐risk patients receiving current COG standard treatment including tandem stem cell transplants and immunotherapy following induction, MIBG relative scores on bone sectors have been integrated into the recent revision of the International Neuroblastoma Response Criteria (INRC) . The relative bone score is the ratio of the Curie scores at response assessment to diagnosis (without the soft‐tissue component).…”
Section: Introductionmentioning
confidence: 99%